2022
DOI: 10.1017/jns.2021.90
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an instrument for perceived factors affecting fruit and vegetable intake based on Pender's health promotion model

Abstract: Increasing fruit and vegetable (F&V) intake has a protective role against chronic conditions such as cardiovascular disease, cancer and diabetes. The present study aimed to validate an instrument for measuring the perception of effective factors on consumption behaviour of F&V based on Pender's health promotion model (HPM).This cross-sectional validation survey has consisted of five steps: literature review in order to plan and develop an instrument, face validity assessment, content validity assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Pender's Health Promotion Model (HPM) (Figure A5) was founded by Dr. Nola Pender in 1982 [40]. Thus, [41], a cross-sectional study, with no evidence level available, stated perceptions of fruit/vegetable consumption impacted by Pender's HPM with the following constructs: "previous relevant behavior, perceived barriers, perceived self-efficacy, behavior-related emotions, perceived benefits, interpersonal influences, situational influences, commitment to an action plan, immediate preferences and demand, motivational factors, and behavioral outcome" [41]. It was concluded that this model was effective to evaluate behavioral outcomes of health promotion [41].…”
Section: Pender's Health Promotion Modelmentioning
confidence: 99%
“…Pender's Health Promotion Model (HPM) (Figure A5) was founded by Dr. Nola Pender in 1982 [40]. Thus, [41], a cross-sectional study, with no evidence level available, stated perceptions of fruit/vegetable consumption impacted by Pender's HPM with the following constructs: "previous relevant behavior, perceived barriers, perceived self-efficacy, behavior-related emotions, perceived benefits, interpersonal influences, situational influences, commitment to an action plan, immediate preferences and demand, motivational factors, and behavioral outcome" [41]. It was concluded that this model was effective to evaluate behavioral outcomes of health promotion [41].…”
Section: Pender's Health Promotion Modelmentioning
confidence: 99%